Value of [18F]FDG PET radiomic features and VEGF expression in predicting pelvic lymphatic metastasis and their potential relationship in early-stage cervical squamous cell carcinoma - Li, Kexin; Sun, Hongzan; Lu, Zaiming; Xin, Jun; Zhang, Le; Guo, Yan; Guo, Qiyong (European journal of radiology, 2018)
The purpose of this study was to explore the value of 2-deoxy-2-[18F]fluoro-d-glucose positron emission tomography/computed tomography ([18F]FDG PET/CT) radiomic features combined with vascular endothelial growth factor (VEGF) expression in predicting pelvic lymphatic metastasis in patients with early-stage cervical squamous cell carcinoma and the added value of radiomic features in predicting VEGF expression. Ninety-four newly diagnosed cervical squamous cell carcinoma patients (training dataset: n = 64, validation cohort: n = 30) in stage Ia to IIa, according to the International Federation of Gynecology and Obstetrics (FIGO) staging system, who underwent [18F]FDG PET/CT were retrospectively analyzed. Radiomic features of the [18F]FDG PET scans were extracted, and the value of the lymph node sizes, metabolic parameters (both tumor and lymph nodes), radiomic features and VEGF expression level in predicting lymphatic metastasis were evaluated by receiver operating characteristics curves (ROC) and were compared using DeLong test. Moreover, we studied the associations between the [18F]FDG PET radiomic features and VEGF expression. Total lesion glycolysis (TLG) and the expression of VEGF were significantly higher in subjects with lymphatic metastasis than in those without. The homogeneity feature derived from the histogram, the skewness, had a certain value in predicting lymphatic metastasis (AUC = 0.803 in training dataset, P < 0.05, 95% CI 0.684, 0.892; AUC = 0.757 in validation dataset, P < 0.05, 95% CI 0.545, 0.904). Additionally, the combination of this radiomic feature and VEGF expression had a significantly superior predictive value (AUC = 0.878, P < 0.05, 95% CI 0.772– 0.947), compared to that of the conventional parameters. Moreover, 26 radiomic features derived from the histogram and GLCM features correlated with VEGF expression. In patients with early-stage cervical squamous cell carcinoma, PLN metastasis can be predicted by TLG and the textural feature of homogeneity. Radiomic features in combination with the VEGF expression level improved the prediction accuracy. In addition, some features derived from the histogram and gray-level co-occurrence matrices (GLCM) may have a certain value in predicting the VEGF expression level.